1995
DOI: 10.1007/bf00187202
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced second-harmonic response and stability of corona-poled guest?host polycarbonate thin films

Abstract: Second-harmonic generation and spectroscopic absorption measurements were made to study the non-linear optical and stability properties of guest/host polycarbonate thin films in which the guest chromophores were oriented by corona poling. Optimum poling conditions were achieved at temperatures less than the glass-rubber transition temperatures. Stabilized order parameters as high as 0.23 and retention of orientational order as high as 86% were found. Stable, resonance-enhanced, values of the non-linear optical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…It may also be possible to induce oriented single crystals and as polymer-dispersed guest/ growth of crystals by either appropriate prohost systems. [6][7][8] Interestingly para-nitroaniline cessing or by the process of polymer-induced crys-(PNA), although it does not exhibit second-order tallization. 13,14 However, for the latter process to effect by itself, has been reported to be nonlinearly take place, the polymer can interact with the optically active when dispersed in polymers such guest molecules through charge transfer (donoras aliphatic polyesters, ultraviolet-cured polyaacceptor type or hydrogen bonding would be necessary).…”
Section: Introductionmentioning
confidence: 98%
“…It may also be possible to induce oriented single crystals and as polymer-dispersed guest/ growth of crystals by either appropriate prohost systems. [6][7][8] Interestingly para-nitroaniline cessing or by the process of polymer-induced crys-(PNA), although it does not exhibit second-order tallization. 13,14 However, for the latter process to effect by itself, has been reported to be nonlinearly take place, the polymer can interact with the optically active when dispersed in polymers such guest molecules through charge transfer (donoras aliphatic polyesters, ultraviolet-cured polyaacceptor type or hydrogen bonding would be necessary).…”
Section: Introductionmentioning
confidence: 98%
“…In the crystalline sample the presence of inter-molecular hydrogen bonding between the DAN molecules is indicated by a small shift but the much larger shifts to lower frequency in both DANdoped PMMA and DAN-doped BPAPC are clear evidence that hydrogen bonds of greater strength than those in the bulk crystal had formed. Wan et al [10] have suggested that hydrogen bonding in PMMA might be somewhat weaker than that in BPAPC and that this accounts in part for the enhanced polar stability of the latter guest-host system. It would be difficult to argue for a significant difference between the hydrogen bond strengths in the two guesthost systems, however, given such a small difference in the resonance position of the N-H stretch.…”
Section: Infra-red Spectroscopic Studiesmentioning
confidence: 99%
“…Both polymers may form hydrogen bonds to the guest but it was our contention that BPAPC has a sufficiently rigid backbone to hold the aligned guest in place. Even in BPAPC, however, the nonlinearity decays as the glass transition temperature, T g , is approached and, in the doped system of our previous work, due to plasticization, the T g dropped to 80 • C. In addition to stability, we observed an apparent enhancement of the optical nonlinearity over that expected using the standard accepted models and by using gas-phase calculations of µ and β. Wan et al [10] subsequently attributed the improvement in stability and enhancement of the nonlinear response found in polycarbonate doped with disperse orange-3-and DR1-doped BPAPC to hydrogen bonding and, furthermore, suggested that hydrogen bonds between the dopant and PMMA might be weaker than those between dopant and polycarbonate backbones.…”
Section: Introductionmentioning
confidence: 99%
“…Many organic compounds, as well as polymers, have been investigated in the past in this respect as single crystals, donor‐acceptor, or guest/host systems 1–3. The various materials, such as para‐nitroaniline (PNA), meta‐nitroaniline (MNA), 2‐methyl 4‐nitroaniline (mNA), and azo benzene derivatives, etc., have been extensively studied for their NLO properties such as second harmonic generation (SHG) and electro‐optic modulation (EO) 4–8. The donor‐acceptor or guest/host systems are superior as compared to single crystals; the advantages being easy processability for large area devices and handling of crystals for application in integrated optics or fibre optics.…”
Section: Introductionmentioning
confidence: 99%